Application of flexible ureteroscopy combined with holmium laser lithotripsy and their therapeutic efficacy in the treatment of upper urinary stones in children and infants - Li, Junhua; Yu, Huiqin; Zhou, Peng; Pan, Huixian; Li, Ruipeng; Wang, Yanbin; Song, Chen; Lou, Yangfeng; Zhu, Jingyu (Urology Journal, 2019)
Purpose: To investigate the efficacy and safety of retrograde intrarenal surgery (RIRS) for the treatment of pediatric patients. Materials and Methods: A total of 45 patients with upper urinary stones treated using flexible ureteroscopy combined with holmium laser lithotripsy at our department between June 2015 and January 2017 were examined in this study. Results: The operative success rate of treatment using holmium laser lithotripsy via flexible ureteroscopy was 97.8% (44/45); one patient (1/45, 2.2%) was converted to laparoscopic pyelolithotomy, and the calculus was successfully removed. Lithotripsy via flexible ureteroscopy was successful during the first phase in 38 patients (38/45, 84.4%), and second or third phase lithotripsy was needed for six patients (6/45, 13.3%). Intraoperative ureteral fracture in the middle and lower sections occurred in one pediatric patient who was converted to laparoscopic pyelolithotomy and ureter bladder reimplantation. This patient was discharged after recovery at 2 weeks postoperative and showed no significant renal dysfunction over the 12-month follow-up period. Severe postoperative gross hematuria occurred in one patient, who improved after hemostasis and other symptomatic treatments. High fever occurred in two patients (body temperature >39°C), who later improved. These pediatric patients were discharged after active anti-infection and other conservative treatments for 4 days. All of the included patients were followed up for 2-15 months, with an average follow-up period of 8 months. The total calculus clearance rate was 100% (45/45), with no recurrence of the calculus. Conclusion: In this study, most upper urinary stones in children and infants were treated successfully with holmium laser lithotripsy applied via flexible ureteroscopy.